“Meet our group!”: : Addressing multiple audiences on the websites of Spanish research groups - Luzón, María José (International Journal of English Studies, 2019)
Websites offer research groups a powerful tool for self-promotion and dissemination of their research to a diversified audience. The aim of this study is to explore how research groups affiliated to a research institution in a non-Anglophone country compose their websites to achieve visibility and impact and reach multiple audiences. Content analysis of the websites and semi-structured interviews were used to examine the language(s) in which the websites are written and their content. The study shows that through these websites research groups address simultaneously the international disciplinary community and various local audiences and that these audiences shape the choice of language and content. Findings from this study provide insights into new communication and representation practices engaged in by research groups to meet disciplinary goals, requirements for funding, and society’s demands.